Pemberdayaan Masyarakat melalui Workshop Kewirausahaan dalam Pengelolaan Limbah Anorganik - Putri, Anindya Cahya; Putri, Fathasyah Aulia; Syaputri, Sri Juhani; Wahyuni, Eka Sri; Yarmunida, Miti (Universitas Pahlawan Tuanku Tambusai, 2025)
Ineffective management of inorganic waste poses environmental and social challenges in many communities. To address this, students from KKN-MBKM UIN FAS conducted an entrepreneurship workshop as a form of community empowerment. The aim was to enhance residents' skills in processing inorganic waste into marketable products, thereby increasing income and environmental awareness. The community service employed the ABCD (Asset-Based Community Development) approach, focusing on utilizing local potentials and resources through direct training, mentoring, and hands-on practice in creating creative products from inorganic waste. The results showed improved participant capabilities in waste management and the emergence of new business opportunities based on waste processing. This activity is significant as it not only reduces waste volume but also promotes economic independence through sustainable entrepreneurship. Thus, the workshop contributes meaningfully to community empowerment and environmental preservation.